Cellulose nanocrystal-graft-polyacrylic acid /polyvinyl alcohol hydrogels: Physicochemical properties and swelling behavior - Nurul Husna, Halim; Lau, Kam Sheng; Nur Fathihah, Jafri; Nursyamimi, Ahmad Ghazali; Rasidi, Roslan; Sarani, Zakaria; Chin, Siew Xian; Chia, Chin Hua (Springer Netherlands, 2024)
This research describes the swelling behavior of cellulose nanocrystal-graft-polyacrylic acid/polyvinyl alcohol (CNC-g-PAA/PVA) hydrogels produced via a semi-interpenetrating network (semi-IPN) approach. To improve the dispersion of cellulose nanocrystals (CNCs) in the hydrogel system, the CNCs were embedded into the PAA polymer structure via grafting with AA monomers and polymerization processes. The produced CNC-g-PAA was further developed into a semi-IPN system with polyvinyl alcohol (PVA) to study the effect of CNC content on the water absorption and retention properties. The physical and chemical properties of the semi-IPN hydrogels were characterized using Fourier transform infrared spectroscopy (FTIR), field emission scanning electron microscopy (FESEM), thermogravimetric analysis (TGA), and rheometer. The data revealed that an increased CNC content significantly improved the swelling ratio and swelling kinetics of the hydrogels at room temperature. Moreover, a higher pH and temperature also enhanced the swelling performance of the hydrogels. These improvements demonstrate the potential utility of CNC-g-PAA/PVA hydrogels in agricultural and horticultural applications.